2015
DOI: 10.1037/a0038387
|View full text |Cite
|
Sign up to set email alerts
|

Work–family conflict, emotional exhaustion, and displaced aggression toward others: The moderating roles of workplace interpersonal conflict and perceived managerial family support.

Abstract: Taking a resource-based self-regulation perspective, this study examined afternoon emotional exhaustion as a mediator linking the within-person relations between morning work-family conflict and later employee displaced aggression in the work and family domains. In addition, it examined resource-related contextual factors as moderators of these relations. The theoretical model was tested using daily diary data from 125 employees. Data were collected at 4 time points during each workday for 3 consecutive weeks.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
219
1
13

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 251 publications
(248 citation statements)
references
References 99 publications
15
219
1
13
Order By: Relevance
“…Although displacing one's anger onto others violates desirable social norms and expectations (e.g., the principle of reciprocity; Bordia, Restubog, & Tang, 2008) and the impulse to displace one's anger ought to be regulated and inhibited (e.g., Bushman et al, 2005), this regulation process may become less effective when employees suffer self-regulation impairment after customer mistreatment. Consequently, employees may find it difficult to regulate their aggressive impulses and may be more likely to lash out at others (i.e., exhibit more displaced aggression), including other customers, coworkers and supervisors at work, and family members at home (e.g., Liu et al, 2015). As such, displaced aggression may serve as a bridge between work life and home life.…”
Section: Behavioral Criteria As Distal Outcomesmentioning
confidence: 95%
“…Although displacing one's anger onto others violates desirable social norms and expectations (e.g., the principle of reciprocity; Bordia, Restubog, & Tang, 2008) and the impulse to displace one's anger ought to be regulated and inhibited (e.g., Bushman et al, 2005), this regulation process may become less effective when employees suffer self-regulation impairment after customer mistreatment. Consequently, employees may find it difficult to regulate their aggressive impulses and may be more likely to lash out at others (i.e., exhibit more displaced aggression), including other customers, coworkers and supervisors at work, and family members at home (e.g., Liu et al, 2015). As such, displaced aggression may serve as a bridge between work life and home life.…”
Section: Behavioral Criteria As Distal Outcomesmentioning
confidence: 95%
“…As commuting strain increases, it consumes more resources, leaving fewer resources available for self‐regulation at work. Supporting this argument, empirical research found that commuting strain is positively related to workplace aggression (Hennessy, ), which has been shown to be a result of impaired capacity of self‐regulation (Y. Liu et al., ; Thau & Mitchell, ; Wang et al., ). Therefore, we propose: Hypothesis 2 :Morning commuting strain is negatively related to subsequent self‐regulation at work. …”
Section: Hypotheses Developmentmentioning
confidence: 98%
“…Specifically, daily task significance refers to the extent to which an employee's work tasks on a particular day have significant impact on other people (Hackman & Oldham, ). Family interference with work refers to the extent to which an employee is distracted from work by family‐related duties on a particular work day (Carlson & Frone, ; Y. Liu et al., ; Wang, Liu, Zhan, & Shi, ). We examine these two variables as potential moderators based on Beal et al.’s () model.…”
mentioning
confidence: 99%
“…Conversely, under low workgroup conflict, employees experience relatively fewer cognitive distractions, and correspondingly fewer demands on their available cognitive control resources. These resources are therefore less likely to be at risk (see Liu et al, 2015), leaving human service workers with greater potential to apply cognitive control resources to forgiveness efforts. However, as previously theorized, human service workers may not have the capacity to forgive due to cognitive impairment at egregious victimization levels, or they may perceive the task of forgiveness as too effortful at these levels to be worth the resource expenditure.…”
Section: Moderating Role Of Workgroup Conflict Between Victimization mentioning
confidence: 99%